Usefulness of Magnetic Resonance Spectroscopy for the Initial Diagnosis of Mitochondrial DNA-Associated Leigh Syndrome - Ji-Hoon Na; Je Hee Shin; Hyunjoo Lee; Young-Mock Lee (Korean Child Neurology Society, 2022)
Purpose Diagnosing Leigh syndrome (LS), a representative mitochondrial disease, remains challenging. Mitochondrial DNA (mtDNA)-associated LS, which is maternally inherited, has relatively well-known genetic variants. We evaluated the usefulness of brain magnetic resonance spectroscopy (MRS) for the initial diagnosis of mtDNA-associated LS using data from LS patients. Methods The study involved LS patients who visited Gangnam Severance Hospital between 2006 and 2018. Based on patients' clinical findings, genetic evaluations, brain magnetic resonance imaging, and brain MRS findings, 24 mtDNA-associated and 49 gene-negative LS patients were included in the current study. Lactate peaks and decreased N-acetyl aspartate (NAA) peaks in brain MRS were compared between both groups. Results In total, 11 mtDNA mutation subtypes were detected. Our findings showed a higher proportion of brain MRS abnormalities in mtDNA-associated LS patients than in gene-negative LS patients, but no statistically significant differences were observed between the two groups (lactate peak, P=0.080; decreased NAA peak, P=0.115). Conclusion Brain MRS is currently limited as an initial diagnostic test for mtDNA-associated LS. However, it may be a useful non-invasive test for the follow-up evaluation of mtDNA-associated LS treatment. Ultra-high-field MRS technology is expected in the future.